2016
DOI: 10.1007/s10815-016-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative markers in cryopreservation medium from frozen-thawed embryos: a possible tool for improved embryo selection in in vitro fertilization?

Abstract: Purpose The present study evaluated the association between oxidative parameters in embryo cryopreservation medium and laboratory and clinical outcomes. Methods This prospective laboratory study was conducted in an IVF unit in a university-affiliated hospital with 91 IVF patients undergoing a frozen-thawed embryo transfer cycle. Following thawing, 50 μL of embryo cryopreservation medium was retrieved from each cryotube and tested by the thermochemiluminescence (TCL) assay. TCL amplitudes after 50 (H1), 150 (H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…These include dilution of sperm samples (and seminal fluid), exposure to toxic cryoprotectants, and pH and osmotic changes induced by cooling to cryogenic temperatures and rewarming for thawing. In line with this, a significantly increased ROS production has been reported in human gametes, as well as in mice and human embryos, during cryopreservation [61][62][63][64]. In contrast, the formation of ice crystals is lower when vitrification is performed, with lower osmotic shock due to ultra-rapid cooling [65].…”
Section: Embryo Cryopreservationmentioning
confidence: 74%
“…These include dilution of sperm samples (and seminal fluid), exposure to toxic cryoprotectants, and pH and osmotic changes induced by cooling to cryogenic temperatures and rewarming for thawing. In line with this, a significantly increased ROS production has been reported in human gametes, as well as in mice and human embryos, during cryopreservation [61][62][63][64]. In contrast, the formation of ice crystals is lower when vitrification is performed, with lower osmotic shock due to ultra-rapid cooling [65].…”
Section: Embryo Cryopreservationmentioning
confidence: 74%
“…We also hypothesize that the suboptimal embryos may express oxidative stress in the cryopreservation medium, and higher oxidative stress levels are associated with lower implantation rates. 24 Therefore, we think that the implantation rate for optimal day-3 embryo transfers after 2 h of culture can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Although the embryo culture medium has been optimized to resemble that of the uterus, there is still the potential for this post‐thawing culture to have adverse effects on the embryo 8 . It was suggested that embryos might respond poorly to the culture medium and be susceptible to oxidative stress, leading to lower implantation rates 9 . Some studies have shown that post‐warming embryo culture for 2–5 h results in higher implantation and live birth rates than culturing overnight 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…8 It was suggested that embryos might respond poorly to the culture medium and be susceptible to oxidative stress, leading to lower implantation rates. 9 Some studies have shown that post-warming embryo culture for 2-5 h results in higher implantation and live birth rates than culturing overnight. 10,11 However, other studies showed no differences in clinical outcomes between the short and long culture duration groups.…”
mentioning
confidence: 99%